PENINGKATAN KEMAMPUAN MENULIS TEKS ARGUMENTATIF MELALUI PENDEKATAN PROJECT BASED LEARNING - Nurani Ayu Febriana; Testiana Deni Wijayatiningsih; Erna Setyawati (LitbangMu Jawa Tengah and Teacher Professional Education UNIMUS, 2025)
This study aims to improve the argumentative text writing skills of 12th-grade students in class XII F at SMA N 11 Semarang through the implementation of the Project-Based Learning (PjBL) model. Writing argumentative texts is an essential competency for students to develop critical, logical, and systematic thinking skills. However, initial observations revealed that students' ability to write argumentative texts was relatively low. This research employed a Classroom Action Research (CAR) approach using the model developed by Kemmis and McTaggart, which consists of four stages: planning, implementation, observation, and reflection. The research subjects were 36 students from class XII F at SMA N 11 Semarang in the academic year 2024/2025. Data were collected through observation, interviews, writing tests, and documentation. The data were analyzed descriptively using qualitative and quantitative methods. The findings show that implementing the Project-Based Learning model significantly improved students' argumentative writing skills. In Cycle I, the average student writing score was 70, which increased to 82 in Cycle II. Additionally, students' motivation and participation levels also showed significant improvement. Based on these results, it can be concluded that the Project-Based Learning model is effective in enhancing the argumentative writing skills of 12th-grade students in class XII F at SMA N 11 Semarang.